Evanescent eosinophilic gastritis in recurrent Helicobacter pylori infection - Nasa, Mukesh; Patel, Jignesh; Choksey, Ajay; Patel, Bhumit; Phadke, Aniruddha; Sawant, Prabha (Journal of Digestive Endoscopy, 2013)
Eosinophilic gastroenteritis is characterized histologically by eosinophilic infiltration of the gut wall and clinically manifests by gastrointestinal (GI) symptoms. A high index of suspicion is required for the early diagnosis of this uncommon disease in patients who have concomitant GI symptoms and peripheral eosinophilia. This unusual case who initially had duodenal ulcer with duodenal stenosis, responded to Helicobacter pylori treatment and dilatation. He was symptom free for 2 years. Subsequently, developed evanescent eosinophilic gastritis and recurrent H. pylori infection with refractory prepyloric ulceration, but no duodenal stenosis. Eosinophilic gastritis and H. pylori infection initially responded to treatment, but subsequently the patient developed nonhealing prepyloric ulcer and refractory H. pylori infection and had persistent symptoms; all these necessitated surgical intervention consisting of antrectomy with gastrojejunostomy.
Keywords: Antrectomy; duodenal stenosis; duodenal ulcer; eosinophilic gastroenteritis; H. pylori; refractory H. pylori infection